Photocatalytic and photoelectrochemical systems for oxidation of aromatic compounds in an aqueous environment - Ng, Yun Ru (Nanyang Technological University, 2020)
As the demand for chemical products increases, alongside a rising problem of pollution due to chemical wastes, there is great interest in developing systems that can resolve either or both issues in a sustainable way. Inspired by nature, the development of photocatalytic and photoelectrochemical (PEC) systems had been pursued as a possible solution. In this work, both a PEC system involving nanoporous bismuth vanadate (BiVO4) with tetraamidomacrocyclic ligand iron complexes (Fe-TAML) as co-catalysts and a photocatalytic system involving modified graphitic carbon nitrides (g-C3N4) were investigated. Both systems were also applied to the oxidation of bisphenol compounds, as well as the oxidation of lignin in lignocellulose. In addition, a hydrophobic metal halide perovskite photocatalytic system was explored for C-C bond cleavage and dehydrogenation reactions, while tetraamidomacrocyclic ligand cobalt complexes (Co-TAML) were investigated for hydrogen evolution reaction.